An Analysis of Debating First Principles in The Debaters’ Speech - Teguh Adimarta; Dewi Tumatul Ainin; Rama Juni Pratama (Jurnal Sains Sosio Humaniora, 2019)
This study examined the implementation of debate competition first principles in the grand final of a debate competition.. Using the result of open-response questionnaires distributed to the adjudicator and 6 participants of the grand final of the debate competition, the researchers then inteviewed and discussed the debate transcript and the result of open-response questionnaires with some triangulators from the perspective of debate first principles. The interview was done to capture deeper perceptions that could be gained. The study reported that there were some first principles used by the debaters to strengthen their arguments. This research finding also proved that how useful the implementation of first principle, not only to strengthen the argument but also to rebut the opponent team argument.